2016
DOI: 10.1073/pnas.1525749113
|View full text |Cite
|
Sign up to set email alerts
|

Roles of density-dependent growth and life history evolution in accounting for fisheries-induced trait changes

Abstract: The relative roles of density dependence and life history evolution in contributing to rapid fisheries-induced trait changes remain debated. In the 1930s, northeast Arctic cod (Gadus morhua), currently the world's largest cod stock, experienced a shift from a traditional spawning-ground fishery to an industrial trawl fishery with elevated exploitation in the stock's feeding grounds. Since then, age and length at maturation have declined dramatically, a trend paralleled in other exploited stocks worldwide. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 87 publications
4
85
0
Order By: Relevance
“…A negatively sloped PMRN indicates that individuals who grow slowly have a greater tendency to mature at a smaller size than fast‐growing individuals (Heino & Dieckmann, ). Other modeling studies have predicted little evolution of PMRN slopes in response to harvest (Dunlop, Heino et al, ; Eikeset et al, ). Superficially, the shift to a negative sloped PMRN for yellow perch in MU1 where harvest declined somewhat but remained high relative to other MUs is consistent with the effects of size‐selective harvest (Figure ).…”
Section: Discussionmentioning
confidence: 97%
“…A negatively sloped PMRN indicates that individuals who grow slowly have a greater tendency to mature at a smaller size than fast‐growing individuals (Heino & Dieckmann, ). Other modeling studies have predicted little evolution of PMRN slopes in response to harvest (Dunlop, Heino et al, ; Eikeset et al, ). Superficially, the shift to a negative sloped PMRN for yellow perch in MU1 where harvest declined somewhat but remained high relative to other MUs is consistent with the effects of size‐selective harvest (Figure ).…”
Section: Discussionmentioning
confidence: 97%
“…In experimental studies of captive Menidia menidia , harvesting of large fish leads to the evolution of slower growth rates, whereas harvesting of small fish leads to the evolution of faster growth rates (Conover & Munch, 2002). Evolutionary models show that fishing mortality can favor higher or lower growth rate, depending on the size selectivity of fishing mortality and other factors (Dunlop, Heino et al., 2009; Eikeset et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Eco‐genetic modeling also has been used to explore how different intensities of density‐dependent growth affect population dynamics and stock productivity (Gobin, Lester, Fox, & Dunlop, 2016). Intrinsic growth rate also has been treated as a decision variable in models of size‐selective fisheries (Dunlop, Heino et al., 2009; Eikeset et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of our modelling approach is the absence of population regulation 624 through density-dependent processes, which is a key ingredient of alternative individual-based eco-genetic models of fisheries-induced evolution (Dunlop et al 626 2015b;Eikeset et al 2016). A previous modelling study that examined the impact of a range of density-dependent processes acting on fecundity and mortality on selection 628 31 differentials on reproductive investment in pike (Esox lucius) (Arlinghaus et al 2009) indeed found that the predictions were rather sensitive to density-dependent somatic 630 growth but insensitive to density-dependent mortality.…”
Section: Model Limitationsmentioning
confidence: 99%